Discovery of new 1H-pyrazolo[3,4-d]pyrimidine derivatives as anticancer agents targeting EGFRWT and EGFRT790M - Ahmed A. Gaber; Mohamed Sobhy; Abdallah Turky; Hanan Gaber Abdulwahab; Ahmed A. Al-Karmalawy; Mostafa. A. Elhendawy; Mohamed. M. Radwan; Eslam B. Elkaeed; Ibrahim M. Ibrahim; Heba S. A. Elzahabi; Ibrahim H. Eissa (Taylor & Francis Group, 2022)
New 1H-pyrazolo[3,4-d]pyrimidine derivatives were designed and synthesised to act as epidermal growth factor receptor inhibitors (EGFRIs). The synthesised derivatives were assessed for their in vitro anti-proliferative activities against A549 and HCT-116 cancer cells. Compounds 8, 10, 12a, and 12b showed potent anti-proliferative activities. Compound 12b was the most promising member with IC50 values of 8.21 and 19.56 µM against A549 and HCT-116, respectively. Compounds 8, 10, 12a, and 12b were evaluated for their kinase inhibitory activities against wild EGFR (EGFRWT). Compound 12b was the most potent member showing an IC50 value of 0.016 µM. In addition, compound 12b showed noticeable activity against mutant EGFR (EGFRT790M) (IC50 = 0.236 µM). Flow cytometric analyses revealed that compound 12b is a good apoptotic inducer and can arrest the cell cycle at S and G2/M phases. Furthermore, it produced an 8.8-fold increase in BAX/Bcl-2 ratio. Molecular docking studies were carried out against EGFRWT and EGFRT790M.